Degradation behaviour of the mechanical properties of bovine cortical bone - Daras, Nicholas (Department of Mechanical Engineering, 2025)
Cortical bone, is subject to extensive mechanical characterization, yet the literature reveals notable discrepancies in reported mechanical properties, in particular concerning the elastic modulus. This variability is attributed to the intricate nature of bone and the diverse experimental factors influencing its performance, notably specimen preparation, including machining techniques and storage protocols. Additionally, the manner in which machine compliance is accounted for is not always reported, particularly concerning the quasi-brittle nature of cortical bone. Even when compliance is accounted for, the methods are not elaborated on in great detail. A further critical observation is the absence of an intermediary step in bone testing simulations, bridging the gap between specimen-scale material characterization and full bone testing. An intermediate stage would provide validation data for a nuanced understanding of material behaviour while mitigating computational expense associated with full bone simulations. To address these gaps, this thesis develops solutions that enhance the accuracy and reliability of the mechanical testing of bone. A custom subpress has been designed and commissioned to minimize machine compliance during quasi-static compression tests on small cortical bone specimens. By quantifying machine compliance through novel methodologies, this research has unveiled its significant impact on mechanical property measurements. Furthermore, this investigation delves into the effects of long-term storage, particularly frozen storage, on bovine cortical bone properties. Three distinct storage protocols were evaluated over a one-year period, revealing significant degradation of fresh bone samples beyond six months irrespective of storage method. This study sheds light on the practical implications of specimen storage protocols in preserving bone integrity. In parallel, the efficacy of cross-section bone specimen tests as an intermediary validation step for simulations is presented. Dynamic strain rate tests using a three-point bending split Hopkinson bar yield rich datasets, indicating clear trends applicable for numerical validation. Simulations utilizing dynamic compression and cross-section data exhibit encouraging correlations with experimental observations. A comparison between the material model for cortical bone in the commonly used ‘Total Human Model for Safety' (THUMS) and a strain-rate dependent plasticity material model highlights the advantages of the latter, emphasizing the potential for enhanced simulation accuracy.